Is music listening an effective intervention for reducing anxiety? A systematic review and meta-analysis of controlled studies. (June 2023) - Harney, Cristina; Johnson, Judith; Bailes, Freya; Havelka, Jelena
Anxiety is the most commonly diagnosed mental health disorder in the EU and 18% of the US population experiences an anxiety disorder at any one time. However, only 20% of individuals experiencing anxiety receive a formally administered intervention, highlighting a need for evidence-based interventions that can be self-administered. Music listening can be flexibly self-administered and may be useful for anxiety reduction, but further evidence is needed. The current paper addressed this by conducting the first systematic review and meta-analysis of controlled studies testing music listening interventions for naturally occurring state anxiety. A protocol was registered on PROSPERO ID: CRD42018104308. Searches were carried out of the Cochrane Library, Ovid MEDLINE, PsycINFO, Embase, Web of Science and CINAHL databases, yielding 6208 records. After screening for eligibility, 24 controlled studies were included in the review and 21 were included in the meta-analysis. Results of the meta-analyses showed that music listening had an overall significant large effect on alleviating anxiety ( d = −0.77 [95% CI = −1.26, −0.28], k = 21). It was concluded that music listening is effective for reducing anxiety in a range of groups. Further research should focus on clinical groups with diagnosed mental health problems.